Urinary Tract Infections and Bacterial Multidrug Resistance in Kidney Transplant Impact on Function and Graft Survival (2025)
Objective: This study aimed to evaluate the sociodemographic, clinical, paraclinical, and microbiological characteristics of kidney transplant recipients with and without urinary tract infection (UTI) and determine their impact on renal function and graft survival in a referral center in Atlántico, Colombia. Methods: We conducted a retrospective, observational, analytical study including 163 kidney transplant recipients between 2015 and 2020. Clinical and microbiological variables were compared according to UTI status. Renal function was assessed using estimated glomerular filtration rate (eGFR). Graft survival was analyzed with Kaplan–Meier curves, and predictors of graft loss were identified using Cox regression models. Results: UTI prevalence was 17.8% (29/163), with a higher proportion of women in the UTI (+) group compared to the UTI (−) group (62% vs. 34%, p = 0.004). Escherichia coli (59%) and Klebsiella spp. (31%) were the predominant pathogens, with MDR in 66% of isolates and carbapenem resistance in 28%. Patients with UTIs had significantly lower baseline and follow-up eGFR (p ≤ 0.002), yet five-year graft survival was comparable (93% vs. 91%, p = 0.54). Baseline eGFR (HR: 0.95, p < 0.001) and institutional referral (HR: 9.7, p = 0.010) were independent predictors of graft loss, whereas UTIs were not associated with increased risk. Conclusions: Post-transplant UTIs in Atlántico were characterized by high antimicrobial resistance and reduced renal function, but did not affect graft survival. Antimicrobial stewardship and institutional optimization strategies are essential to improve outcomes in this vulnerable population.